Glass fiber reinforced PET composite material and preparation method thereof
By grafting the modified glass fibers on the surface of the glass fiber and adding them to the modifier, the shortcomings of traditional glass fiber reinforced PET composites in interface bonding strength and impact resistance are solved, and the overall performance of the composite materials is significantly improved.
Patent Information
- Application Number
- CN202510386725.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-31
AI Technical Summary
Traditional glass fiber reinforced PET composites have shortcomings in interface bonding strength and impact resistance, resulting in limited application of their applications in lightweight structural parts.
Modified glass fibers are used to graft thiol groups on the surface of the glass fibers by KH-580 coupling agent to form thiolated glass fibers, and the terminal hydroxy quaternary ammonium salt is formed by reaction of tert-butyldimethylamine and 2-bromoethanol. Then, it is replaced with octene trichlorosilane to form a modifier. The alkyl-containing long chain and thiol addition of the modifier is used to enhance the binding performance of the glass fibers and PET.
Through the use of modified glass fibers, the interface combination performance and impact resistance between PET and glass fibers are significantly enhanced, solving the contradiction between strength improvement and impact resistance of traditional materials, and improving the overall performance of composite materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer composite materials, and in particular relates to a glass fiber reinforced PET composite material and a preparation method thereof. Background Art
[0002] Polyethylene terephthalate (PET) is a high-performance engineering plastic with excellent mechanical strength, heat resistance and chemical stability; glass fiber is an inorganic non-metallic material with the advantages of high strength, high modulus, heat resistance and corrosion resistance; the material composited with PET and glass fiber has high strength and modulus, can replace some metal materials, and is widely used in lightweight structural parts.
[0003] Traditional glass fiber reinforced PET composites improve mechanical properties through the interface bonding between fibers and matrix, but there are the following problems: the polar ester group of the PET molecular chain has limited interaction with the hydroxyl group on the surface of the glass fiber, resulting in low interface bonding strength and poor stress transfer efficiency. In addition, high content of glass fiber can easily lead to reduced melt fluidity, affecting the molding process. The use of coupling agent to treat the glass fiber only through simple physical adsorption or single chemical bond connection cannot effectively buffer the impact energy, resulting in a contradiction between the existing glass fiber reinforced PET composite materials in terms of strength improvement and impact resistance, which seriously restricts the application of this composite material. Summary of the invention
[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide a glass fiber reinforced PET composite material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A glass fiber reinforced PET composite material comprises the following raw materials in parts by weight: 100 parts of PET masterbatch, 32-45 parts of modified glass fiber, 0.19-0.24 parts of nucleating agent, 1.6-2 parts of lubricant and 0.12-0.15 parts of antioxidant.
[0006] The modified glass fiber is prepared by the following method: Step A1: premix tert-butyldimethylamine, 2-bromoethanol and anhydrous acetonitrile, heat to 70-80°C, slowly add triethylamine and stir to react for 4-5h, and remove acetonitrile by rotary evaporation to obtain a hydroxy-terminated quaternary ammonium salt; Further, the dosage ratio of tert-butyldimethylamine, 2-bromoethanol, triethylamine and anhydrous acetonitrile is 0.1 mol: 0.11-0.12 mol: 4-6 mL: 50-65 mL, and triethylamine promotes the quaternization reaction of 2-bromoethanol and tert-butyldimethylamine. The specific reaction route is as follows:
[0007] Step A2: Mix the terminal hydroxyl quaternary ammonium salt and anhydrous tetrahydrofuran, introduce dry nitrogen for protection, control the water bath temperature at 5-15° C., add octene trichlorosilane and stir to react for 2.5-3 hours, then heat potassium hydroxide and reflux for 1-1.5 hours, remove tetrahydrofuran by rotary evaporation, wash the substrate with water, and dry it to obtain a modifier; Further, the amount ratio of octyl trichlorosilane, terminal hydroxyl quaternary ammonium salt, potassium hydroxide and anhydrous tetrahydrofuran is 0.1 mol: 0.3 mol: 2-3 g: 130-160 mL, and the terminal hydroxyl quaternary ammonium salt is substituted with octyl trichlorosilane to form a compound with a branched tert-butyl end. The specific reaction route is as follows:
[0008] Step A3: Mix silane coupling agent KH-580, acetic acid and ethanol aqueous solution, add short chopped glass fiber and impregnate for coupling for 24 hours, and dry the material to obtain mercaptolated glass fiber; Furthermore, the dosage ratio of the chopped glass fiber, the silane coupling agent KH-580, the acetic acid and the ethanol aqueous solution is 50g:3.5-4.5mL:1.2-1.6mL:80-100mL, the volume fraction of the ethanol aqueous solution is 30%, and the silane coupling agent KH-580 is hydrolyzed and coupled to the surface of the chopped glass fiber to introduce organic thiol groups to the surface.
[0009] Step A4: Mix the modifier, photoinitiator and dioxane, spray the mixture onto the surface of the thiolated glass fiber, and send it into a UV curing machine to control the UV irradiation intensity to 450-600mW / cm 2 , the temperature is 80-100°C, the reaction is carried out for 0.8-1.2h, and the modified glass fiber is obtained after spray cleaning and drying; Furthermore, the usage ratio of the thiolated glass fiber, the modifier, the photoinitiator and the dioxane is 50g:1.9-2.4g:20-30mg:25-30mL. Under UV initiation, the modifier is added to the organic thiol group on the surface of the thiolated glass fiber, and the modifier is combined with the glass fiber through the alkyl chain containing the thioether structure.
[0010] Furthermore, the lubricant is pentaerythritol stearate.
[0011] Furthermore, the antioxidant is used in combination of the antioxidant 1010 and the antioxidant 168.
[0012] A preparation method of a glass fiber reinforced PET composite material comprises the following steps: PET masterbatch, a nucleating agent, a lubricant and an antioxidant are mixed and fed from a main feeding port of an extruder, modified glass fiber is fed from a side feeding port, plasticized, extruded and pelletized at 260-270°C to obtain a glass fiber reinforced PET composite material.
[0013] Beneficial effects of the present invention: The invention adopts a modified glass fiber reinforced PET to prepare a composite material. The modified glass fiber is prepared by grafting a mercapto group on the surface of the glass fiber with KH-580 to prepare a mercaptolated glass fiber. Tertiary hydroxyl quaternary ammonium salt is formed by reacting tert-butyl dimethylamine and 2-bromoethanol, and then substituted with octyl trichlorosilane to form a modifier. The alkenyl group containing a long alkyl chain introduced into the modifier molecule is added to the surface-grafted mercapto group to introduce the modifier molecule into the surface of the glass fiber. Compared with the existing glass fiber reinforced PET, the modified glass fiber is introduced into the bonding interface between the PET and the glass fiber. The quaternary ammonium structure carries a positive charge, while the ester group in the PET molecular chain contains negatively charged oxygen atoms. The two form an electrostatic interaction, which enhances the interfacial compatibility and bonding performance. The modifier introduces a branched tert-butyl structure to the surface of the glass fiber, which is entangled with the non-polar chain segments of PET, synergistically enhancing the mechanical interlocking of the interface and improving the strengthening effect of the glass fiber. On the other hand, the branched tert-butyl group forms a micro-support structure at the bonding interface to disperse the impact stress. The alkyl segment containing the thioether structure absorbs the impact energy through molecular chain slippage, which significantly improves the impact resistance of the composite material. DETAILED DESCRIPTION
[0014] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0015] Example 1, preparation of glass fiber reinforced PET composite material, the specific implementation process is as follows: (1) Preparation of modified glass fiber Step A1: premix tert-butyldimethylamine, 2-bromoethanol and anhydrous acetonitrile, heat to 80°C, stir at 150rpm and slowly add triethylamine to react for 4h, wherein the amount ratio of tert-butyldimethylamine, 2-bromoethanol, triethylamine and anhydrous acetonitrile is 0.1mol:0.12mol:6mL:65mL, and remove acetonitrile by rotary evaporation to obtain terminal hydroxyl quaternary ammonium salt.
[0016] Step A2: Mix the terminal hydroxyl quaternary ammonium salt and anhydrous tetrahydrofuran, introduce dry nitrogen for protection, control the temperature of the water bath at 15°C, add octene trichlorosilane, stir and react at 90rpm for 2.5h, then reflux the potassium hydroxide at the temperature for 1h, wherein the amount ratio of octene trichlorosilane, terminal hydroxyl quaternary ammonium salt, potassium hydroxide and anhydrous tetrahydrofuran is 0.1mol:0.3mol:3g:160mL, remove tetrahydrofuran by rotary evaporation, wash the substrate with water, and dry it to obtain a modifier.
[0017] Step A3: prepare an ethanol aqueous solution with a volume fraction of 30%, take a mixture of silane coupling agent KH-580, acetic acid and ethanol aqueous solution, and then add chopped glass fiber for impregnation coupling for 24 hours, wherein the amount ratio of chopped glass fiber, silane coupling agent KH-580, acetic acid and ethanol aqueous solution is 50g:4.5mL:1.6mL:100mL, and dry the material to obtain thiolated glass fiber.
[0018] Step A4: Mix the modifier, photoinitiator and dioxane, spray the mixture onto the surface of the thiolated glass fiber, and send it into a UV curing machine to control the UV irradiation intensity to 600mW / cm 2 , the temperature is 100°C, and the irradiation baking reaction is carried out for 0.8h, wherein the usage ratio of thiolated glass fiber, modifier, photoinitiator and dioxane is 50g:2.4g:30mg:30mL. Finally, it is sprayed with water for cleaning and dried to obtain modified glass fiber.
[0019] (2) Preparation of composite materials The raw materials are calculated by weight: 100 parts of PET masterbatch, using TRN-8385FC resin masterbatch raw material; 32 parts of modified glass fiber, which is homemade in this embodiment; 0.24 parts of nucleating agent, using JW-30 commercially available nucleating agent; 1.6 parts of lubricant, using industrial grade pentaerythritol stearate; 0.12 parts of antioxidant, using antioxidant 1010 and antioxidant 168 in a weight ratio of 2:1; The PET masterbatch, nucleating agent, lubricant and antioxidant were mixed at a high speed of 600 rpm for 15 minutes in a high-speed mixer, the mixture was fed from the main feeding port of the extruder, and the modified glass fiber was fed from the side feeding port. The mixture was plasticized, extruded and pelletized at 260°C to obtain a glass fiber reinforced PET composite material.
[0020] Example 2, preparing a glass fiber reinforced PET composite material, the specific implementation process is as follows: (1) Preparation of modified glass fiber Step A1: premix tert-butyldimethylamine, 2-bromoethanol and anhydrous acetonitrile, heat to 70°C, stir at 120rpm and slowly add triethylamine to react for 5h, wherein the amount ratio of tert-butyldimethylamine, 2-bromoethanol, triethylamine and anhydrous acetonitrile is 0.1mol:0.11mol:4mL:50mL, and remove acetonitrile by rotary evaporation to obtain terminal hydroxyl quaternary ammonium salt.
[0021] Step A2: Mix the terminal hydroxyl quaternary ammonium salt and anhydrous tetrahydrofuran, introduce dry nitrogen for protection, control the temperature of the water bath to 5°C, add octene trichlorosilane, stir and react at 60rpm for 3h, then reflux the potassium hydroxide at the temperature for 1.5h, wherein the amount ratio of octene trichlorosilane, terminal hydroxyl quaternary ammonium salt, potassium hydroxide and anhydrous tetrahydrofuran is 0.1mol:0.3mol:2g:130mL, remove tetrahydrofuran by rotary evaporation, wash the substrate with water, and dry it to obtain a modifier.
[0022] Step A3: prepare an ethanol aqueous solution with a volume fraction of 30%, take a mixture of silane coupling agent KH-580, acetic acid and ethanol aqueous solution, and then add chopped glass fiber for impregnation coupling for 24 hours, wherein the amount ratio of chopped glass fiber, silane coupling agent KH-580, acetic acid and ethanol aqueous solution is 50g:3.5mL:1.2mL:80mL, and dry the material to obtain thiolated glass fiber.
[0023] Step A4: Mix the modifier, photoinitiator and dioxane, spray the mixture onto the surface of the thiolated glass fiber, and send it into a UV curing machine to control the UV irradiation intensity to 450mW / cm 2 , the temperature is 80°C, and the irradiation baking reaction is carried out for 1.2 hours, wherein the usage ratio of thiolated glass fiber, modifier, photoinitiator and dioxane is 50g:1.9g:20mg:25mL. Finally, it is sprayed with water for cleaning and dried to obtain modified glass fiber.
[0024] (2) Preparation of composite materials The raw materials are calculated by weight: 100 parts of PET masterbatch, using TRN-8385FC resin masterbatch raw material; 45 parts of modified glass fiber, which is homemade in this embodiment; 0.19 parts of nucleating agent, using JW-30 commercially available nucleating agent; 2 parts of lubricant, using industrial grade pentaerythritol stearate; 0.15 parts of antioxidant, using antioxidant 1010 and antioxidant 168 in a weight ratio of 2:1; The PET masterbatch, nucleating agent, lubricant and antioxidant were mixed at a high speed of 600 rpm for 15 minutes in a high-speed mixer, the mixture was fed from the main feeding port of the extruder, and the modified glass fiber was fed from the side feeding port. The mixture was plasticized, extruded and pelletized at 270°C to obtain a glass fiber reinforced PET composite material.
[0025] Example 3, preparation of glass fiber reinforced PET composite material, the specific implementation process is as follows: (1) Preparation of modified glass fiber Step A1: premix tert-butyldimethylamine, 2-bromoethanol and anhydrous acetonitrile, heat to 75°C, stir at 150rpm and slowly add triethylamine to react for 4.5h, wherein the amount ratio of tert-butyldimethylamine, 2-bromoethanol, triethylamine and anhydrous acetonitrile is 0.1mol:0.12mol:5mL:60mL, and remove acetonitrile by rotary evaporation to obtain terminal hydroxyl quaternary ammonium salt.
[0026] Step A2: Mix the terminal hydroxyl quaternary ammonium salt and anhydrous tetrahydrofuran, introduce dry nitrogen protection, control the temperature of the water bath to 10°C, add octene trichlorosilane, stir and react at 90rpm for 2.8h, then reflux the potassium hydroxide at the temperature for 1.2h, wherein the amount ratio of octene trichlorosilane, terminal hydroxyl quaternary ammonium salt, potassium hydroxide and anhydrous tetrahydrofuran is 0.1mol:0.3mol:3g:150mL, remove tetrahydrofuran by rotary evaporation, wash the substrate with water, and dry it to obtain a modifier.
[0027] Step A3: prepare an ethanol aqueous solution with a volume fraction of 30%, take a silane coupling agent KH-580, acetic acid and an ethanol aqueous solution and mix them, then add short glass fibers and soak and couple them for 24 hours, wherein the amount ratio of short glass fibers, silane coupling agent KH-580, acetic acid and ethanol aqueous solution is 50g:4mL:1.4mL:90mL, and dry the material to obtain thiolated glass fibers.
[0028] Step A4: Mix the modifier, photoinitiator and dioxane, spray the mixture onto the surface of the thiolated glass fiber, and send it into a UV curing machine to control the UV irradiation intensity to 550mW / cm 2 , the temperature is 90°C, and the irradiation baking reaction is carried out for 1 hour, wherein the usage ratio of thiolated glass fiber, modifier, photoinitiator and dioxane is 50g:2.2g:25mg:30mL, and finally it is sprayed with water for cleaning and dried to obtain modified glass fiber.
[0029] (2) Preparation of composite materials The raw materials are calculated by weight: 100 parts of PET masterbatch, using TRN-8385FC resin masterbatch raw material; 38 parts of modified glass fiber, which is homemade in this embodiment; 0.22 parts of nucleating agent, using JW-30 commercially available nucleating agent; 1.8 parts of lubricant, using industrial grade pentaerythritol stearate; 0.13 parts of antioxidant, using antioxidant 1010 and antioxidant 168 in a weight ratio of 2:1; The PET masterbatch, nucleating agent, lubricant and antioxidant were mixed at a high speed of 600 rpm for 15 minutes in a high-speed mixer, the mixture was fed from the main feeding port of the extruder, and the modified glass fiber was fed from the side feeding port. The mixture was plasticized, extruded and pelletized at 260°C to obtain a glass fiber reinforced PET composite material.
[0030] Example 4, preparation of glass fiber reinforced PET composite material, the specific implementation process is as follows: (1) Preparation of modified glass fiber Step A1: premix tert-butyldimethylamine, 2-bromoethanol and anhydrous acetonitrile, heat to 80°C, stir at 150rpm and slowly add triethylamine to react for 4.2h, wherein the amount ratio of tert-butyldimethylamine, 2-bromoethanol, triethylamine and anhydrous acetonitrile is 0.1mol:0.11mol:5mL:55mL, and remove acetonitrile by rotary evaporation to obtain terminal hydroxyl quaternary ammonium salt.
[0031] Step A2: Mix the terminal hydroxyl quaternary ammonium salt and anhydrous tetrahydrofuran, introduce dry nitrogen for protection, control the temperature of the water bath to 5°C, add octene trichlorosilane, stir and react at 90rpm for 3h, then reflux the potassium hydroxide for 1h, wherein the amount ratio of octene trichlorosilane, terminal hydroxyl quaternary ammonium salt, potassium hydroxide and anhydrous tetrahydrofuran is 0.1mol:0.3mol:3g:150mL, remove tetrahydrofuran by rotary evaporation, wash the substrate with water, and dry it to obtain a modifier.
[0032] Step A3: prepare an ethanol aqueous solution with a volume fraction of 30%, take a mixture of silane coupling agent KH-580, acetic acid and ethanol aqueous solution, and then add chopped glass fiber for impregnation coupling for 24 hours, wherein the amount ratio of chopped glass fiber, silane coupling agent KH-580, acetic acid and ethanol aqueous solution is 50g:4mL:1.5mL:100mL, and dry the material to obtain thiolated glass fiber.
[0033] Step A4: Mix the modifier, photoinitiator and dioxane, spray the mixture onto the surface of the thiolated glass fiber, and send it into a UV curing machine to control the UV irradiation intensity to 500mW / cm 2 , the temperature is 90°C, and the irradiation baking reaction is carried out for 1.1 hours, wherein the usage ratio of thiolated glass fiber, modifier, photoinitiator and dioxane is 50g:2.1g:30mg:30mL. Finally, it is sprayed with water for cleaning and dried to obtain modified glass fiber.
[0034] (2) Preparation of composite materials The raw materials are calculated by weight: 100 parts of PET masterbatch, using TRN-8385FC resin masterbatch raw material; 40 parts of modified glass fiber, which is homemade in this embodiment; 0.21 parts of nucleating agent, using JW-30 commercially available nucleating agent; 1.8 parts of lubricant, using industrial grade pentaerythritol stearate; 0.14 parts of antioxidant, using antioxidant 1010 and antioxidant 168 in a weight ratio of 2:1; The PET masterbatch, nucleating agent, lubricant and antioxidant were mixed at a high speed of 600 rpm for 15 minutes in a high-speed mixer, the mixture was fed from the main feeding port of the extruder, and the modified glass fiber was fed from the side feeding port. The mixture was plasticized, extruded and pelletized at 270°C to obtain a glass fiber reinforced PET composite material.
[0035] In Comparative Example 1, referring to Example 4, the modified glass fiber was replaced by mercaptolated glass fiber in equal amounts, and the rest of the implementation process was exactly the same.
[0036] Comparative Example 2, referring to Comparative Example 1, one portion of RQT-TG2885 toughening agent is added to the raw materials of the composite material, and the toughening agent is blended with the PET masterbatch, and the rest of the implementation process is exactly the same.
[0037] Samples were taken from the composite material prepared as above and injection molded into specimens. The tensile test was carried out according to ASTM D638-2022, the bending test was carried out according to ASTM D790-17, the impact test was carried out according to ASTM D256-24, and the melt mass flow rate test was carried out according to ASTM D1238-23 (270°C / 2.16kg). The specific test results are shown in Table 1: Table 1
[0038] It can be seen from the test data in Table 1 that the composite material prepared in the embodiment has higher tensile strength and flexural strength, the reinforcing effect of glass fiber on PET is significant, and the composite material maintains high impact resistance, has a high melt mass flow rate, and is easy to process and shape.
[0039] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0040] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A glass fiber reinforced PET composite material, characterized in that: The raw materials include the following by weight: 100 parts of PET masterbatch, 32-45 parts of modified glass fiber, 0.19-0.24 parts of nucleating agent, 1.6-2 parts of lubricant and 0.12-0.15 parts of antioxidant; The modified glass fiber is prepared by the following method: Step A1: premix tert-butyldimethylamine, 2-bromoethanol and anhydrous acetonitrile, heat to 70-80°C, slowly add triethylamine and stir to react for 4-5h to obtain a hydroxy-terminated quaternary ammonium salt; Step A2: Mix the terminal hydroxyl quaternary ammonium salt and anhydrous tetrahydrofuran, introduce dry nitrogen for protection, control the water bath temperature at 5-15° C., add octene trichlorosilane and stir to react for 2.5-3 hours, then heat potassium hydroxide and reflux for 1-1.5 hours to obtain a modifier; Step A3: Mix silane coupling agent KH-580, acetic acid and ethanol aqueous solution, add short chopped glass fiber and impregnate for coupling for 24 hours, and dry the material to obtain mercaptolated glass fiber; Step A4: Mix the modifier, photoinitiator and dioxane, spray the mixture onto the surface of the thiolated glass fiber, and send it into a UV curing machine to control the UV irradiation intensity to 450-600mW / cm 2 , temperature is 80-100°C, reaction time is 0.8-1.2h, spray cleaning and drying are performed to obtain modified glass fiber.
2. A glass fiber reinforced PET composite material according to claim 1, characterized in that: The usage ratio of tert-butyldimethylamine, 2-bromoethanol, triethylamine and anhydrous acetonitrile is 0.1 mol: 0.11-0.12 mol: 4-6 mL: 50-65 mL.
3. A glass fiber reinforced PET composite material according to claim 2, characterized in that: The usage ratio of octyl trichlorosilane, terminal hydroxyl quaternary ammonium salt, potassium hydroxide and anhydrous tetrahydrofuran is 0.1 mol: 0.3 mol: 2-3 g: 130-160 mL.
4. The glass fiber reinforced PET composite material according to claim 3, characterized in that: The usage ratio of the chopped glass fiber, the silane coupling agent KH-580, the acetic acid and the ethanol aqueous solution is 50g:3.5-4.5mL:1.2-1.6mL:80-100mL.
5. The glass fiber reinforced PET composite material according to claim 4, characterized in that: The usage ratio of mercaptolated glass fiber, modifier, photoinitiator and dioxane is 50g:1.9-2.4g:20-30mg:25-30mL.
6. The glass fiber reinforced PET composite material according to claim 1, characterized in that: The lubricant is pentaerythritol stearate.
7. The glass fiber reinforced PET composite material according to claim 1, characterized in that: The antioxidant is a combination of antioxidant 1010 and antioxidant 168.
8. A method for preparing the glass fiber reinforced PET composite material according to any one of claims 1 to 7, characterized in that: Specifically, PET masterbatch, nucleating agent, lubricant and antioxidant are mixed and fed from the main feeding port of the extruder, and modified glass fiber is fed from the side feeding port, plasticized, extruded and pelletized at 260-270°C to obtain a glass fiber reinforced PET composite material.
Citation Information
Patent Citations
Polyethylene terephthalate composite material and preparation method for same
CN103724948A
High-strength low-density flame-retardant modified PET (polyethylene glycol terephthalate) material and its preparation method
CN103849121A
Low-temperature-resistant PP composite board and preparation method thereof
CN119220022A
High-gloss high-glass-fiber-content nylon 66 composite material and preparation method thereof
CN119775769A
Oxynitride glass fiber for composite material and fiber-reinforced plastic
JP1993163672A
Cited By
PET environment-friendly material and preparation method thereof
CN120623725A
LCP fiber reinforced composite material
CN121799004A